The Davidic Messiah in Luke-Acts: The Promise and Its Fulfilment in Lukan Christology - Strauss, Mark L. (Tyndale bulletin, 1993)
A dissertation investigating the theme of the coming king from the line of David within Luke's christological 'proclamation from prophecy and pattern' motif.